Asymptotic behavior of stochastic Schrödinger lattice systems driven by nonlinear noise. Issue 2 (3rd March 2020) - Wang, Bixiang; Wang, Renhai
Abstract: We study the random dynamics of the N -dimensional stochastic Schrödinger lattice systems with locally Lipschitz diffusion terms driven by locally Lipschitz nonlinear noise. We first prove the existence and uniqueness of solutions and define a mean random dynamical system associated with the solution operators. We then establish the existence and uniqueness of weak pullback random attractors in a Bochner space. We finally prove the existence of invariant measures of the stochastic equation in the space of complex-valued square-summable sequences. The tightness of a family of probability distributions of solutions is derived by the uniform estimates on the tails of the solutions at far field.